GOOD CORPORATE GOVERNANCE IN ASEAN FROM 2011 TO 2021: A LITERATURE REVIEW - Sarah Thalya Suherman (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The purpose of this study is to do the literature review in order to obtain insights toward the growth of Good Corporate Governance (GCG) after ASEAN Corporate Governance Scorecard (ASEAN CG Scorecard) was introduced in ASEAN. This research was conducted in 2022 by conducting a literature review of various research result published during 2011-2021. Besides, the identified GCG can be applied in ASEAN countries. They can assist stakeholders in increasing the likelihood of GCG success and can be adopted for further research.